Flavor and aroma compounds of some exotic tropical fruits and berries: biosynthetic pathways and metabolism - Lasekan, Olusegun Ola (CRC Press, 2016)
The characteristic avor of exotic tropical fruits is one of their most attractive attributes to consumers. In this chapter, the enormous diversity of exotic fruit avors is reviewed. Classifying some of the exotic fruits into two classes on the basis of whether esters or terpenes predominate in the aroma was also attempted. Indeed, as far as exotic tropical fruits are concerned, the majority of fruits have terpenes predominating in their aroma prole.